MATURITY MODEL DEVELOPMENT FOR INFORMATION QUALITY MANAGEMENT (CASE STUDY: SANTO BORROMEUS HOSPITAL) - PRIMA KURNIATI (NIM : 23508030), ANGELINA
Data and information are important corporate assets for achieving business goals and improving competitive advantages. However, data and information management in an organization are usually done by a specific business unit only, without adequate support from the board of management and all other business units within the company. As the result, policy and procedure governing the management of data and information are not well structured. The need of supporting tools is covered as a reactive action against the failure of data and information management. Skills, expertise, responsibility and accountability of the people participating in the management of data and information are often ignored. In addition, goal setting and measurement of the achievement become an overlooked aspect. With these limitations, the company manages data and information case by case. Some methods of data and information management suggest ways that can be taken by companies to resolve the problem faced in the management of data and information. This thesis develops maturity model, as being proposed by SEI (Software Engineering Institute), for data and information management within a company. The maturity model is developed considering six (6) maturity attributes defined by COBIT 4.1, as a best practice that have been proven as applied in various companies. The maturity of data and information management process is determined by assessing the maturity level achieved by each phase of the information lifecycle. Maturity level achieved can be compared with company‟s target maturity level. By using this model, a company can assess at the regular basis the achievement and target of maturity level within the company. The difference between the two levels can be a reference in strategy setting to improve data and information management within the company. To validate the model being developed, the model is implemented to a case study of data and information management in St. Borromeus Hospital. This case study is selected based on the idea that managing data and information in a healthcare institution needs a high quality process. A less optimal management of data and information can create a bad impact for the company, and even for patients of the hospital. The testing is done by distributing questionaires to the participants of data and information management, to define maturity level that has been achieved and targeted in the company. The testing results on the case study show that this model can be used to assess the maturity level of data and information management processes on current condition (as-is) and targeted condition (to-be) as expected by the participants of data and information management within the company. In general, data and information management on St. Borromeus Hospital has reached level 3 (defined) and are being targeted to reach level 4 (quantitatively managed). The analysis of respondents‟ answers on the head and staff shows that the most of the heads tend to give a higher answer than the majority of staff. Moreover, by analyzing questionaire answers per strata we conclude that there are differences in maturity level achievement in some business units. Based on the analysis of questionnaire answers being collected, this thesis proposed some strategies to be implemented in St. Borromeus Hospital to improve the maturity level of data and information management within the company. In addition to the strategy being proposed, this thesis defines key performance indicator (KPI) and key goal indicator (KGI) related to the data and information management process as well as policies and procedures that can be used to administer data and information management in St. Borromeus Hospital.